Vasculite livedóide em doente com síndrome antifosfolípido - Serra, S (2010)
The authors present a clinical case of a 30 year old male patient admitted to the hospital for recurrent cyanosis and feet pain lasting for one year. In addition he presented bilateral purpuric lesions in the lateral maleolar region, one of which with ulceration. The finding of anticardiolipin antibodies associated with intraluminal thrombosis in the dermal vessels, allowed to conclude for Antiphospholipid syndrome. The cutaneous changes identified are named livedoid vasculitis.